Strength and conditioning : a concise introduction - Cissik, John M. (London : Routledge, 2012)
'Strength and Conditioning offers a concise but comprehensive overview of training for athletic performance. Introducing essential theory and practical techniques in all of the core areas of athletic training, the book clearly demonstrates how to apply fundamental principles in putting together effective real-world training programs. While some established textbooks rely on established but untested conventional wisdom, this book encourages students and professionals to think critically about their work and to adopt an evidence-based approach. It is the only introductory strength and conditioning textbook to properly explain the interdependence of aspects of training such as needs analysis, assessment, injury, competition level, athlete age and program design, and the only book to fully explain how those aspects should be integrated.No other textbook offers such an accessible, engaging and reflective introduction to the theory and application of strength and conditioning programs. Including clear step-by-step guidance, suggestions for further reading, and detailed sport-specific examples, this is the perfect primer for any strength and conditioning course or for any professional trainer or coach looking to refresh their professional practice'--Provided by publisher.
Keywords: Physical education and training; Muscle strength; Physical fitness -- Physiological aspects; Athletes -- Training of